A comparative review of maternal and neonatal outcome among pregnant women with COVID-19 in first and second wave in a tertiary care centre of South Rajasthan - Chaudhary, Divya; Chauhan, Madhubala; Gupta, Diksha; Jat, Shivraj (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Corona virus disease 2019 has taken a huge toll over health infrastructure and care all across the world. This article depicts our experience of COVID-19 in pregnant women and analyses maternal and neonatal outcome of same in first and second wave of this pandemic. Aim and objectives of the study were to compare the demographic characteristics, presenting features and fetomaternal outcome in COVID positive pregnant women in first v/s second wave in a tertiary care hospital. Methods: The RTPCR COVID-19 positive pregnant women admitted during the period April-2020 to March-2021 were considered in 1st wave of COVD-19 and that from April-2021 till June-2021 as 2nd wave of COVID-19. Data like baseline characteristics, past medical, obstetric history, clinical presentation, laboratory results, imaging findings, management modalities, maternal and neonatal outcome were analysed and compared. Results: Peak of 1st wave of COVID-19 was found during the months of July-September 2020, while of 2nd in April-June 2021. Most women presented with COVID-19 RTPCR positive were asymptomatic both in 1st and 2nd wave. Though most patients were managed on room air in both waves, 6.52% and 9.38% were on oxygen, 1.09% and 10.94% were managed with mechanical ventilation and BIPAP in 1st and 2nd wave respectively. There was significant (p<0.05) increase in maternal deaths in the 2nd wave (7.03%) as compared to 1st wave (1.09%). Conclusions: A significantly large number of patients were affected in 2nd wave of COVID-19 pandemic with more morbidity and mortality. Neonatal population remained relatively unaffected in both waves.